Toward Quantifying Decentralization of Blockchain Networks With Relay Nodes - Shahsavari, Yahya; Zhang, Kaiwen; Talhi, Chamseddine (Frontiers in Blockchain, 2022)
Permission-less blockchain systems, such as Bitcoin, maintain a distributed ledger by continuously running a distributed consensus algorithm, (e.g., based on Proof-of-Work), over a decentralized P2P network. There have been many research efforts to address scalability and performance issues at the network layer, such as the use of relay networks in Bitcoin. However, very few works analyze the impact of the network topology on decentralization. Since the latter is a key concept in blockchains, the formal analysis of decentralized blockchain networks is an important research gap we seek to address. In this paper, we present a methodology for quantifying the decentralization degree of a blockchain network. To accomplish this, we use two well-known graph models of Erd\"os-Rény and Barabási–Albert in order to study the blockchain network topology. We then quantify the decentralization degree using the clustering coefficient of our network models. We validate our approach through extensive simulations and analyze the decentralization degree with respect to network parameters such as the number of connections per node and the peer selection algorithm. Our results expose the trade-off between the average shortest path and the decentralization degree. Furthermore, we observe the impact of the average shortest path on the network speed and traffic overhead. Finally, we demonstrate that the presence of hub-like nodes such as relay gateways negatively impacts the decentralization degree of blockchain networks.